Age structure of cohorts of mosquitoes from the field using shortwave infrared spectroscopy before and after ULV adulticide treatment. - Swab, Christopher L; Alto, Barry W; Kluiters, Georgette.; Cornine, Frank H; Telford, Sam R (Tufts University. Tisch Library., 2025)
Keywords: Mosquito, Spectroscopy, Age-structure, Risk assessment, Insecticide.; Springer Open.